2017
DOI: 10.1177/0954407017728159
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective reliability design optimization of a novel side door negative Poisson’s ratio impact beam

Abstract: By possessing a good capacity for energy absorption and a lightweight structure, the negative Poisson's ratio (NPR) structure has very fine prospects for application in vehicle engineering. By combining the traditional side door impact beam and a NPR structure, a novel side door NPR impact beam is first proposed in this work to improve the side impact crashworthiness in automobiles. The performance of the side door NPR impact beam is first studied in detail by comparison with a traditional side door impact bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The results showed that the energy absorption characteristics of the crash box were improved effectively. Zhou et al 23 proposed a novel side door NPR impact beam to improve vehicle side crashworthiness by combining the traditional side door impact beam and NPR structure, and the multi-objective reliability design optimization of the side door NPR impact beam was conducted to further improve crashworthiness. Qi et al 24 studied the auxetic honeycomb-cored sandwich panels with NPR effect under impact and close-in blast.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the energy absorption characteristics of the crash box were improved effectively. Zhou et al 23 proposed a novel side door NPR impact beam to improve vehicle side crashworthiness by combining the traditional side door impact beam and NPR structure, and the multi-objective reliability design optimization of the side door NPR impact beam was conducted to further improve crashworthiness. Qi et al 24 studied the auxetic honeycomb-cored sandwich panels with NPR effect under impact and close-in blast.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional materials, the unique 'auxetic' effect of NPR structures [16,17] gives them many novel mechanical properties [18,19], such as higher shear modulus [20], fracture toughness [21], indentation resistance [22], impact resistance [23], and specific energy absorption [24], which makes NPR structures very promising for aerospace, vehicles, air-delivered packaging, and other fields with a wide range of applications [25]. In particular, it is important to note that the inhomogeneity of NPR materials can significantly alter their impact dynamics [26,27], and the alteration of the unit cell microstructure [28] can also have a significant impact on the macro-and microscopic dynamic stress evolution of the material. Therefore, establishing the relationship between unit cell microstructure and macroscopic impact failure behavior of auxetic porous materials, and then achieving the purpose of tunable design for energy absorption on the basis of good impact resistance, is also one of the frontier topics in the study of dynamic properties of NPR materials [29].…”
Section: Introductionmentioning
confidence: 99%
“…G. Zhou et al [15] applied an enhanced hybrid and adaptive meta-model based global optimization to improve the performance of the steering system. G. Zhou et al [16] proposed a multi-objective optimal algorithm using Latin hypercube sampling technique, orthogonal design, response surface model, radial-based importance sampling technique, and multi-objective particle swarm optimization algorithm to develop novel side door negative Poisson's ratio impact beam. G. Sun et al [17] developed a multi-objective and multi-case reliability-based design optimization based on the radial basis function, the non-dominated sorting genetic algorithm II, and Monte Carlo simulation to optimize the tailor rolled blank hat-shaped structure.…”
Section: Introductionmentioning
confidence: 99%